log(9x) + log(x) = 4log(10)
log(9) + log(x) + log(x) = 4log(10)
2log(x) = 4log(10) - log(9)
log(x2) = log(104) - log(9)
log(x2) = log(104/9)
x2 = 104/9
x = 102/3
x = 33 and 1/3
2 log(x) + 3 log(x) = 105 log(x) = 10log(x) = 10/5 = 210log(x) = (10)2x = 100
It equals 0.4971
If the log of x equals -3 then x = 10-3 or 0.001or 1/1000.
x = 3*log8 = log(83) = log(512) = 2.7093 (approx)
log (6x + 5) = 26x + 5 > 06x + 5 - 5 > 0 - 56x > - 56x/6 > -5/6x > -5/6log (6x + 5) = 210^2 = 6x + 5100 = 6x + 5100 - 5 = 6x + 5 - 595 = 6x95/6 = 6x/695/6 = xCheck:
True
log(x) + log(2) = log(2)Subtract log(2) from each side:log(x) = 0x = 100 = 1
The explanation and answer to the following math equation to find x -0.3 plus 5-5 log (d) equals a plus 5-5 log 4 (d) is -5 log(d)+x+4.7 = a-5 log(4 d)+5. The solution is x = a-6.63147.
log(2) + log(4) = log(2x)log(2 times 4) = log(2x)2 times 4 = 2 times 'x'x = 4
G(x) = log(2x) + 2, obviously!
2
You have, y = 6 + log x anti log of it, 10y = (106) x
log(f) + log(0.1) = 6 So log(f*0.1) = 6 so f*0.1 = 106 so f = 107
It cannot be done because the base for the second log is not given.
How about 8*log(88/88) or 888*log(8/8)
log3 + logx=4 log(3x)=4 3x=10^4 x=10,000/3
Use the identity log(ab) = log a + log b to combine the logarithms on the left side into a single term. Then take antilogarithms (just take the log away) on both sides.